Physical and acoustic properties of petroleum and renewable based polyurethane foam filled with shorea leprosula - Mohd Azahari, Muhammad Shafiq (2018)
Physical and acoustic properties of petroleum-based polyurethane (PU) and renewable based polyurethane (RPU) foam composites filled with Shorea Leprosula (Red Meranti) fiber filler has been investigated. Shorea Leprosula wood dust namely as SL was used as the filler. RPU was used with hope to substitute the current polyurethane. This research was carried out to investigate the physical and acoustical properties and the ability of polymer foam composites (PF) towards sound absorption coefficient (SAC) based on the wood fiber size with range of 150-200 μm (powder), 250-300 μm (fibrous) and 900-1000 μm (flakes). 5 wt%, 10 wt%, 15 wt% and 20 wt% of SL filler content and thickness of 10 mm, 20 mm and 30 mm were used for each PF sample. PF samples have been tested by using Impedance Tube test, Scanning Electron Microscopy (SEM) and Mettler Toledo Density kit. As a result, the sound absorption coefficient (SAC) shows value at achievable frequency range at low (0-1500 Hz) and high (1501-6000 Hz) frequency absorption level. PU with powder fiber size (UP20), average pore size with 425.4 μm (smallest), and density 857.9 kg/m3 (highest) shows better sound behaviour with SAC value of 0.2478 and 0.9598 at low and high frequency absorption level. Meanwhile, for RPU with powder fiber size (RP20), average pore size with 479.8 μm (smallest), and density 839.0 kg/m3 (highest) shows better sound behaviour with SAC value of 0.2478 and 0.9940 at low frequency and high frequency absorption level. Moreover, UP20 and RP20 give the highest SAC value with 30 mm in thickness 0.9037 and 0.9909, and 0.9784 and 0.9809 at low and high frequency absorption level respectively. In conclusion, acoustical characteristics of PF samples shows the ability to influence the absorption coefficient of polymeric foam at different frequency levels. Both type of PF produce is suitable for sound absorbing materials for indoor and outdoor sound applications.